Quorum sensing and other collective regenerative behavior in organ populations. (October 2016) - Widelitz, Randall; Chuong, Cheng-Ming
Abstract : Stem cell and microenvironment molecular interactions have been studied in detail but regenerative behavior at the organ population level has remained unexplored. Organ renewal can occur continuously or in cyclic episodes. Progenitors may be distributed as one entity or compartmentalized into multiple units. Multiple units offer advantages as each unit can be regulated differently in different body regions or physiological stages, adapting animals to their niche with flexible functional forms. Using the hair paradigm, we show how periodic patterning can convert one morphogenetic field into many hair germs, how follicles can be renewed with different cycle times and phenotypes in a region-specific manner, and how new properties, such as regenerative waves and quorum sensing, emerge to coordinate collective regenerative behavior.